The Influence of Organizational Culture and Work Discipline on Employee Organizational Behavior at the Investment and One-Stop Integrated Service Office of Lahat Regency - Kurnia Lita Ovita Sari; Darwin Kesuma; Mujari Mujari (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2026)
This study aims to determine how organizational culture and work discipline partially and simultaneously influence employee organizational behavior at the Investment and One-Stop Integrated Service Office of Lahat Regency. The sample size for this study was 42 respondents. The sampling method used was incidental sampling. This quantitative study employed multiple linear regression analysis, processed using SPSS, resulting in a regression equation . The results of this study indicate a significant influence between organizational culture and employee organizational behavior at the Investment and One-Stop Integrated Service Office of Lahat Regency. There is also a significant influence between work discipline and employee organizational behavior at the Investment and One-Stop Integrated Service Office of Lahat Regency. The F-test indicates that organizational culture and work discipline simultaneously influence employee organizational behavior at the Investment and One-Stop Integrated Service Office of Lahat Regency.